2020
DOI: 10.1016/j.heliyon.2020.e03508
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model and socioeconomic and demographic determinants of under-five mortality in Sierra Leone

Abstract: is among the countries that recorded high under-five child mortality rate in the world. To design and implement policies that can address this public health challenge, the present study developed a predictive model of factors that explained under-five mortality in Sierra Leone using the 2008 and 2013 Sierra Leone Demographic and Health Survey (SDHS) datasets. LASSO regression technique was used to select the predictors to build the under-five predictive single-level logit and multilevel logit models. Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
22
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 26 publications
12
22
3
1
Order By: Relevance
“…Poverty, region, and poor education are the major drivers of infant mortality in Nigeria in agreement with several other studies [5,8,15,19]. Poverty is a factor because parents who cannot afford quality care are likely to delay use of facility-based care in the hope that their infants' health will improve with the use of traditional medicine or care with drugs purchased from Patent Medicine Vendors [29].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Poverty, region, and poor education are the major drivers of infant mortality in Nigeria in agreement with several other studies [5,8,15,19]. Poverty is a factor because parents who cannot afford quality care are likely to delay use of facility-based care in the hope that their infants' health will improve with the use of traditional medicine or care with drugs purchased from Patent Medicine Vendors [29].…”
Section: Discussionsupporting
confidence: 83%
“…Proximate predictors of child deaths include sociodemographic factors [5][6][7][8], biomedical factors such as birth interval, weight and gestation period, sex of child and diseases [9][10][11][12][13][14][15][16] and health-seeking behavior and barriers to care [17,18]. Research shows that education, income, and access to healthcare resources (including safe drinking water and sanitation) enhance child survival globally [5-8, 10, 15, 19, 20], and countries having higher inequality in access to education, income and healthcare resources also have higher mortality rates [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Children who were perceived as small-or very-small-sized after birth by their mothers had a higher likelihood of U5M than those perceived as average-or larger-sized. This result contradicts a study performed by Yaya et al [10]; however, few other similar studies showed a significant relationship with U5M [25,[55][56][57][58]. Even if our outcome on perceived children's size was significant, the rationale mothers applied in estimating their children's size after birth remains unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…The selection of predictor variables that influence neonatal mortality was based on the conceptual framework for the study of child survival in developing countries and predictor variables used in previous studies [14][15][16] and available in the 2014 GDHS datasets. The explanatory variables selected for the analysis included sex of child, birth type, birth interval, health insurance status of mother, size of child, maternal age, ever terminated pregnancy, mode of delivery, maternal marital status, parity, household size, maternal religion, wealth index, and prenatal care assistance.…”
Section: Independent Variablesmentioning
confidence: 99%